Halal logistics in Brunei: current constraints and future potentials / Mohamed Syazwan Ab Talib - Ab Talib, Mohamed Syazwan (Universiti Teknologi Mara Selangor, 2020)
Identifying and understanding the constraints and potentials of halal logistics in Brunei Darussalam is integral towards the development of Brunei’s halal economy. Relevant extant literature was analysed using an inductive reasoning approach, where five issues were identified to have had constrained halal logistics in Brunei Darussalam. Three areas that have the potential to stimulate halal logistics were also identified. It is hoped that the findings could benefit future research, as well as academics and practitioners alike, both in the halal logistics sector and the halal research domain, particularly the logistics body of knowledge.